The Agroeconomy of Early Urban Areas in South-Eastern Lithuania in the 13th–14th Centuries: A Case Study of Merkinė - Karaliūtė, Rūta; Buržinskas, Žygimantas; Ananyevskaya, Elina; Motuzaitė Matuzevičiūtė, Giedrė (Archaeologia Lituana, 2025)
This article presents archaeobotanical and zooarchaeological material from Merkinė settlement dating back to the 13th–14th centuries, collected during archaeological excavations in 2023. The analysed material covers not only a historically important period for the formation of the Lithuanian state, but also falls into a transitional climatic period characterised by temperature fluctuations, specifically, – a transition from the Medieval Warm Period to the Little Ice Age. A detailed analysis of the 13th–14th century bioarchaeological material reveals the diversification of agriculture through crop rotation, which ensured successful cultivation of plants in the poor soil of Southeastern Lithuania during this period of climatic change.